(-7)-(-2)-9=x

Simple and best practice solution for (-7)-(-2)-9=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-7)-(-2)-9=x equation:


Simplifying
(-7) + -1(-2) + -9 = x
-7 + -1(-2) + -9 = x

Multiply -1 * -2
-7 + 2 + -9 = x

Combine like terms: -7 + 2 = -5
-5 + -9 = x

Combine like terms: -5 + -9 = -14
-14 = x

Solving
-14 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-14 + -1x = x + -1x

Combine like terms: x + -1x = 0
-14 + -1x = 0

Add '14' to each side of the equation.
-14 + 14 + -1x = 0 + 14

Combine like terms: -14 + 14 = 0
0 + -1x = 0 + 14
-1x = 0 + 14

Combine like terms: 0 + 14 = 14
-1x = 14

Divide each side by '-1'.
x = -14

Simplifying
x = -14

See similar equations:

| -6-1=-32y+32 | | 16-(-13)-(-5)=x | | 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 | | 6(x+2)+4=-6 | | 52x=104 | | 8y-5=6y+7 | | -33m-14=85 | | 5x+5x+3+8=5x+4+4x | | -r+259=-124 | | -2x^2+12x+3=0 | | 3(3+2r)=5-6(r+2) | | 3(2x-4)=5(x+6) | | 7x-6-4x=4x-3 | | 2.1x+1=7 | | 9x-3x=-26+2 | | 7-7x=29x+21 | | 17X^43=100000 | | 145-13= | | 6x+4-4=20 | | 2(w+6)+4=2w+16 | | 75+13w=335 | | 9m=3(8m+30) | | 10+2x-x^2=0 | | 9x+9=11x-3 | | 81-6x=7x | | 9x(x+1)=10 | | 1-2x=3x-9 | | -4x-12=2x+12 |

Equations solver categories